Pengembangan E-LKPD Keanekaragaman Hayati Berbasis Proyek untuk Meningkatkan Keterampilan Abad 21 Siswa dalam Mendukung Pencapaian SDGs - Anliana; Diky Setya Diningrat; Aswarina Nasution (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to develop project-based digital worksheets (E-LKPD) integrated with the Sustainable Development Goals (SDGs) on the topic of biodiversity to enhance students’ 21st-century skills (4Cs). The method used was Research and Development (R&D) with the 4D model through stages of expert validation, interviews, and questionnaires, as well as data analysis using validity tests, N-Gain, and t-tests. The results showed that the E-LKPD had a very high feasibility level (≥92%) and was effective in improving 4C skills, ranging from moderately effective to effective across all aspects. The t-test revealed a significant difference between pretest and posttest results (Sig. < 0.001). Additionally, the E-LKPD was rated as very engaging by students (91.60%) and very practical by teachers (95.70%). Thus, PjBL-based E-LKPD integrated with the SDGs is feasible and effective for use in biodiversity education to enhance 21st-century skills.  Keywords: Biodiversity, E-LKPD, Project-Based Learning (PjBL), SDGs, 4C Skills